Performance of Broiler Chickens with Different Administration Periods of Encapsulated Turmeric (Curcuma domestica Val) Extract as a Natural Feed Additive - Rido, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This study aimed to determine the effect of the administration period of encapsulated turmeric extract (Curcuma domestica Val.) in replacing the role of antibiotic growth promoters (AGPs) in the diet on the performance of broiler chickens. The study used 100 unsexed MB 202 Platinum strain broiler chickens. The housing used was a box-type cage measuring 70 × 60 × 70 cm per unit, with a total of 20 units. An experimental method was applied using a Completely Randomized Design (CRD) consisting of 5 treatments and 4 replications. The treatments were as follows: A = control diet, B = control diet + zinc bacitracin, C = control diet + 0.75% encapsulated turmeric extract administered daily, D = control diet + 0.75% encapsulated turmeric extract administered every two days, and E = control diet + 0.75% encapsulated turmeric extract administered every three days. The diet was formulated to be iso-protein (22%) and iso-caloric (3000 kcal/kg). Parameters measured included feed intake, body weight gain, and feed conversion ratio of broiler chickens. The analysis of variance showed that the use of encapsulated turmeric extract had a significant effect (P<0.05) on body weight gain and feed conversion ratio but had no significant effect (P>0.05) on feed intake. It can be concluded from this study that the performance of broiler chickens fed a diet containing 0.75% encapsulated turmeric extract administered every three days was able to replace AGPs in broiler production.